Overall survival by clinical risk category for high dose interleukin-2 (HD IL-2) treated patients with metastatic renal cell cancer (mRCC): data from the PROCLAIMSM registry. Issue 1 (27th March 2019) - Fishman, M.; Dutcher, J. P.; Clark, J. I.; Alva, A.; Miletello, G. P.; Curti, B.; Agarwal, Neeraj; Hauke, R.; Mahoney, K. M.; Moon, H.; Treisman, J.; Tykodi, S. S.; et al.
Abstract : Background: Prognostic scoring systems are used to estimate the risk of mortality from metastatic renal cell carcinoma (mRCC). Outcomes from different therapies may vary within each risk group. These survival algorithms have been applied to assess outcomes in patients receiving T-cell checkpoint inhibitory immunotherapy and tyrosine kinase inhibitor therapy, but have not been applied extensively to patients receiving high dose interleukin-2 (HD IL-2) immunotherapy. Methods: Survival of 810 mRCC patients treated from 2006 to 2017 with high dose IL-2 (aldesleukin) and enrolled in the PROCLAIM SM registry data base was assessed utilizing the International Metastatic RCC Database Consortium (IMDC) risk criteria. Median follow-up is 23.4 months (mo.) (range 0.2–124 mo.). Subgroup evaluations were performed by separating patients by prior or no prior therapy, IL-2 alone, or therapy subsequent to IL-2. Some patients were in two groups. We will focus on the 356 patients who received IL-2 alone, and evaluate outcome by risk factor categories. Results: Among the 810 patients, 721 were treatment-naïve (89%) and 59% were intermediate risk. Overall, of the 249 patients with favorable risk, the median overall survival (OS) is 63.3 mo. and the 2-year OS is 77.6%. Of 480 patients with intermediate risk, median OS is 42.4 mo., 2-year OS 68.2%, and of 81 patients with poor risk, median OS 14 mo., 2-year OS 40.4%. Among those who received IL-2 alone (356 patients), median OS is 64.5, 57.6, and 14 months for favorable, intermediate and poor risk categories respectively. Two year survival among those treated only with HD IL-2 is 73.4, 63.7 and 39.8%, for favorable, intermediate and poor risk categories respectively. Conclusions: Among mRCC patients treated with HD IL-2, all risk groups have median and 2-year survival consistent with recent reports of checkpoint or targeted therapies for mRCC. Favorable and intermediate risk (by IMDC) patients treated with HD IL-2 have longer OS compared with poor risk patients, with most durable OS observed in favorable risk patients. Favorable risk patients treated with HD IL-2 alone have a 2-year OS of 74%. These data continue to support a recommendation for HD IL-2 for patients with mRCC who meet eligibility criteria. Trial registration: PROCLAIM, NCT01415167 was registered with ClinicalTrials.gov on August 11, 2011, and initiated for retrospective data collection until 2006, and prospective data collection ongoing since 2011.